The Discourse of COVID-19 Variants on COVID-19 News on The Jakarta Post - Semartini, Atur (Linguistics and ELT Journal, 2023)
News always implies ideological background and social condition that produces it. News as popular media continuously constructs reality which is then believed to be the truth by the audience or readers. Pandemic COVID-19 has become an issue that attracts media as well as newspaper. The infection rate of COVID-19 keeps increasing due to the variants that continue to emerge. This research aims to investigate how COVID-19 variants, especially Delta and Omicron variants, are constructed on The Jakarta Post. The data used in this paper is the headline news about COVID-19 variants (Delta and Omicron) on The Jakarta Post during 2021-2022. The data was analyzed using Fairclough’s Critical Discourse Analysis. The analysis confirms that Delta Variant was constructed as deadly virus that caused so many problems in Indonesia, while Omicron Variant was represented as virus that was less harmful than Delta Variant. These findings imply the ideological background and social condition in Indonesia during the pandemic COVID-19. The media emphasized the government’s and society’s role during the pandemic COVID-19.